Ni(II)-catalyzed asymmetric alkenylations of ketimines - Mao Quan (Nature Portfolio, 2018)
Chiral allylic amines are often encountered in bioactive compounds and can be conveniently transformed into other chiral amines. Here, the authors report nickel-catalyzed enantioselective addition and addition/ring-expansion of alkenylboronic acids to ketimines providing a range of valuable chiral azaheterocycles.